Effect of rotation system on irrigated potato crop (Mongolian Journal of Agricultural Sciences, 2021)
In our country average precipitation is annually 250-300 mm, and when we assuming that we need 47.6-43.0 mm precipitation for getting 1 tons of potato and thus means it is sufficient for 6-7tons  yield For more yield use irrigation systems to provide the fields with enough water and humidity is important issue. Cultivation using rotation is not only for producing high yields but also it is important for stabilizing and improving the soil fertility like the first condition of the soil. Irrigated potato fields have a special effect on reducing diseases and increasing yields, lengthening the rotation in the crop rotation sector, increasing the crop structure in rotation, and the use of alternating green manure. The 3-field rotation with green manure has a total yield of 32.0 t / ha, which is 5.4-14.2 t / ha higher than other crop rotations, and the standard yield is 95.7 percent, which is 0.6-5.9 percent higher than other crop rotations. Усалгаатай талбайн төмсний ургацад сэлгээний нөлөөМанай орны хувьд жилд дунджаар 250-300 мм хур тунадас ордог бөгөөд 1 тонн төмс авахад 40.0-50.0 мм хур тунадас орох шаардлагатай гэж үзвэл 6-7 тонн ургац авахад хангалттай гэсэн үг юм.[3] Илүү их ургац авахын тулд тариалангийн талбайг хангалттай хэмжээний ус, чийгээр хангахын тулд усалгааны системийг ашиглах нь чухал асуудал юм. Ээлжлэн тариалалт хийх нь ургац нэмэгдүүлэхээс гадна хөрснийг хамгаалах, хөрсний үржил шимийг тогтворжуулах, сайжруулахад чухал ач холбогдолтой юм.Усалгаатай төмсний талбайд өвчлөлийг бууруулж, ургацыг нэмэгдүүлэхэд ээлжлэн тариалалтын эргэлтийг уртасгах, сэлгээнд байгаа таримлын бүтцийг нэмэгдүүлэх мөн сэлгээд ногоон бордуурт уринш хэрэглэх нь онцгой нөлөөтэй. Ногоон бордуурт уринш оролцсон 3-талбайт сэлгээ нь нийт ургац 32.0 т/га байж бусад сэлгээний хувилбараас 5.4-14.2 т/га илүү,  стандарт ургацын эзлэх хувь 95.7 хувь байж бусад ээлжлэн тариалах  хувилбарт 0.6-5.9 хувиар давуу байна. Түлхүүр үг: сэлгээ, төмс, ургац, өвчин, ногоон бордуурт